Synthesis of potential antiexudative preparations for 2-((4-amino-5-(furan-2-il)-1,2,4-triazole-(4H)-3-yl)-sulfanyl)-N-acetamide series - Chalenko, Natalia; Demchenko, Anatoly; Syrova, Ganna (ScienceRise: Pharmaceutical Science, 2019)
Aim. Conduct the purposeful synthesis of new potential biologically active substances of derivatives of 2 - ((4-amino-5- (furan-2-yl) -1,2,4-triazol (4H) -3-yl) -sulfanyl) -N-acetamides and evaluate their anti-exudative activity on the model of formalin edema in rats. Materials and methods. In this work, standard methods of organic synthesis, physical and chemical methods of proofing the structure of synthesized compounds, elemental analysis, 1H NMR spectroscopy, chromatographic mass spectrometry, and antiexudative activity were studied on the model of formalin edema in rats using a digital plethysmometer. Results. By alkylation of 2-((4-amino-5-(furan-2-yl))-4H-1,2,4-triazole-3-thione with N-aryl-substituted α-chloroacetamides in ethanol in an alkaline medium, (4-amino-5-(furan-2-yl)-1,2,4-triazole(4H)-3-yl)-sulfanyl)-N-acetamide. After crystallization we obtained white or light yellow crystalline substances with clear melting temperatures. On the model of formalin edema in rats, the antiexudative activity of the newly synthesized 2-((4-amino-5-(furan-2-yl)-1,2,4-triazole (4H) -3-yl) -sulfanil)-N-acetamides was studied. According to the results of the research, a dependence between "chemical structure – antiexudative activity" of the first synthesized compounds was established. The results of experimental studies showed that fifteen out of twenty one compounds showed anti-exudative activity, eight of which exceeded this activity or were at the reference level of sodium diclofenac. Conclusions. Synthesis of twenty one compounds of 2-((4-amino-5- (furan-2-yl)-1,2,4-triazole(4H)-3-yl)-sulfanyl)-N-acetamide derivatives was carried out and an evaluation of antiexudative activity, the dependence "chemical structure - antiexudative activity" was established. Leading compounds for antiexudative activity were found